UNIT SHIFT ON TOURISM DAILY NEWS FROM ENGLISH INTO BAHASA INDONESIA : A TRANSLATION STUDY - Ananda Rosintya Putri (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2023)
This study aims to analyze the application of unit shifts in the translation of daily newsabout the Karisma Nusantara Event from English to Bahasa Indonesia. The qualitativedescriptive method used is translation analysis, with a special focus on shifting translationunits with A.P.Catford's theory. This shift includes words, phrases, and sentences in the newstext. This study also explains the difference between Isolated Unit Shift and Unit Shift inCategory Shift. The data was taken from existing daily news by making notes with samplingtechnique analysis and then analyzing the shift in units of English as the Source Language (SL)to Indonesian as the Target Language (TL). The results show that there were 3 downwardranking shifts and 2 upward ranking shift of the 5 data obtained from the news, namelyIsolated Unit Shift.